LARGE-SCALE LITHOGEOCHEMICAL EXPLORATION OF URANIUM DEPOSITS ON CHMEL'NIK AREA - Makarenko, M.; Karly, V.; Stepanuk, M.; Kolyada, V.; Patalakha, M.; Kupenko, I.; Gurin, O.; Kornienko, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The description of the geological structure of Chmel'nik area which is promising for vein-stockwork uranium deposits is presened in the article. The large-scale lithogeochemical prospecting was used for the first time in Ukraine. It based upon a subsoil geochemical survey testing accompanied by representative soil layer allowed to generally estimate the area and determine the sites which show promise for uranium deposit detection.